PENGARUH LEVERAGE; LIKUIDITAS, SAHAM PUBLIK DAN KOMITE AUDIT INDEPENDEN TERHADAP LUAS PENGUNGKAPAN SUKARELA DALAM LAPORAN Ta,TAl HlYUatNAN - Mujiyono Mujiyono; Magdalena Nany (Fakultas Bisnis UKDW, 2007)
Company's aniual report is one of the information that connecting the company's management and their stockholders. The study about voluntary disclosure in an.annual report will provide some insight about disclosure practiees in Indonesian firms. The objective of this research was to give empirical evidence about the effects of leverage, liquidity,firm public own proportion and independent audit committee proportion on voluntary disclosure both partially and simultaneously. Seventy four companies were analyed by multiple regression analysis. The resul*show that leverage insigniJicantly hat positive effect on voluntarydisclosure. Liquidity also insignificantly has positive effect on voluntary diselosure. Butfirm publi own proportion insignificantly has negative effect on voluntary disclosure. Independent audit committee proportion also insigniJicantly has negative effect on voluntary disclosure. The result also show that leverage, liquidity, firm public own proportion and independent audit commitiee pioportion simultaneousiy have insignificant effect on voluntary disclosureKqwords: annual report, vol4ntary disclosure, leverage, tiquidity,finn public own proportion, independent audit committeeproportion